Investigation of magnetic field enriched surface enhanced resonance Raman scattering performance using Fe3O4@Ag nanoparticles for malaria diagnosis - Yuen, Clement (2014)
Recently, we have demonstrated the magnetic field-enriched surface-enhanced resonance Raman spectroscopy (SERRS) of β-hematin by using nanoparticles with iron oxide core and silver shell (Fe3O4@Ag) for the potential application in the early malaria diagnosis. In this study, we investigate the dependence of the magnetic field-enriched SERRS performance of β-hematin on the different core and shell sizes of the Fe3O4@Ag nanoparticles. We note that the core and shell parameters are critical in the realization of the optimal magnetic field-enrich SERRS β-hematin signal. These results are consistent with our simulations that will guide the optimization of the magnetic SERRS performance for the potential early diagnosis in the malaria disease.